Kekosongan Jabatan Kepala Daerah dan Problematika Penunjukan Pelaksana Tugas - Adrianus Handy Harsono (E-Jurnal SPIRIT PRO PATRIA, 2026)
The arrest of several regional heads less than one year after assuming office following the 2024 Regional Elections has generated significant constitutional and administrative implications in Indonesia. This situation creates a vacancy in regional leadership and raises complex legal questions concerning the appointment and authority of Acting Regional Heads under Law Number 23 of 2014 on Regional Government. This study incorporates the case highlighted by the Komite Pemantauan Pelaksanaan Otonomi Daerah (KPPOD) reporting that three regional heads elected in the 2024 Regional Elections were arrested by the Komisi Pemberantasan Korupsi within less than one year of assuming office (KPPOD, 2026). The arrests — involving allegations of bribery, extortion, and the trading of positions — underscore persistent issues of high political campaign costs and weak accountability mechanisms in local governance that continue to undermine effective implementation of Law No. 23 of 2014. The recurrence of anti-corruption interventions shortly after inauguration highlights the systemic risk of corruption and institutional vulnerability in the governance of regional leadership, adding empirical urgency to the legal analysis (KPPOD, 2026). This research aims to analyze the normative framework governing the filling of vacancies in regional leadership, examine the legal status and limitations of Acting Regional Heads, and evaluate the implications of such appointments on democratic legitimacy, regional autonomy, and administrative stability. The study employs a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials include Law Number 23 of 2014, Law Number 10 of 2016 concerning Regional Head Elections, Law Number 18 of 2003 concerning Advocates, and related implementing regulations. Secondary materials consist of recent scholarly articles indexed in Sinta and Scopus. The findings demonstrate that although the statutory framework provides procedural mechanisms for appointing Acting Regional Heads, regulatory ambiguities remain regarding the scope of authority, democratic accountability, and central government intervention. Furthermore, the study highlights the tension between administrative continuity and democratic legitimacy, particularly when Acting Regional Heads exercise strategic policy powers. The research concludes that regulatory harmonization and clearer limitations of authority are essential to safeguard regional autonomy and uphold principles of constitutional governance.